Endogenous technological change, innovation diffusion and transitional dynamics in a nonlinear growth model - Nijkamp, Peter; Poot, Jaques (School of Management Working Papers, 1992)
This paper addresses capital accumulation and capital productivity change in an economy with endogenous technological change and floors and ceilings in activity. The properties of the resulting two-variable nonlinear differential equation system are studied in some detail. The welfare implications are also considered. When discrete lags are introduced, wide-ranging behaviour emerges, which includes convergence to a steady-state, catastrophes, hysteresis, limit cycles and chaos. Simulations illustrate the results. It is found that external shocks, such as the diffusion of innovations from elsewhere, do not just change the level of the steady-state equilibrium but also the dynamical properties of the paths of output and productivity.